Do You Know What Your Scribe Did Last Spring? The Impact of COVID-19 on Medical Scribe Workflow - Gold, Jeffrey A.; Becton, James; Ash, Joan S.; Corby, Sky; Mohan, Vishnu (Applied Clinical Informatics, 2020)
Objective To understand the impact of the shift to virtual medicine induced by coronavirus disease 2019 (COVID-19) has had on the workflow of medical scribes.Design This is a prospective observational survey-based study.Setting This study was conducted at academic medical center in the United States.Participants Seventy-four scribes working in ambulatory practices within an academic medical center.Interventions All medical scribes received a survey assessing their workflow since beginning of COVID-19 restrictions.Primary and Secondary Outcomes To assess the current workflow of medical scribes since transition to virtual care. Secondary outcomes are to assess the equipment used and location of their new workflow.Results Fifty-seven scribes completed the survey. Overall 42% of scribes have transitioned to remote scribing with 97% serving as remote scribes for remote visits. This workflow is conducted at home and with personal equipment. Of those not working as scribes, 46% serve in preclinic support, with a wide range of EHR-related activities being reported. The remaining scribes have been either redeployed or furloughed.Conclusion The rapid transition to virtual care brought about by COVID-19 has resulted in a dramatic shift in scribe workflow with the adoption of a previously unreported workflow of remote scribing for virtual care. Additional work is now needed to ensure these new workflows are safe and effective and that scribes are trained to work in this new paradigm.
Keywords: medical scribe; COVID-19; electronic health record; telemedicine; virtual care